IN VITRO α-AMYLASE AND α-GLUCOSIDASE INHIBITOR ACTIVITY OF ABUTILON INDICUM LEAVES - Pant, Geetika; Sai, Krishna; Babasaheb, S; Reddy, Rajashekar; G, Sibi (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Postprandial hyperglycemia caused by the hydrolysis of carbohydrates by pancreatic α-amylase and intestinal α-glucosidase is a serious condition and inhibition of these enzymes is an effective way in the management of diabetes mellitus. Abutilon indicum (L.) Sweet leaves were used to determine their in vitro α-amylase and α-glucosidase inhibitory activity. Various concentrations from 10 µg ml-1 to 160 µg ml -1 were prepared in methanol along with the standard antidiabetic drug, acarbose. There was a dose dependent percent inhibition by the extract against α-amylase (7.12% - 41.31%) and α-glucosidase (8.01% - 36.13%). Logarithmic regression analysis revealed the IC50 of 129.89 µg ml-1 (α-amylase) and 137.61 µg ml-1 (α-glucosidase) with a potency and preference for α-amylase over α-glucosidase inhibition by the A. indicum leaf extract.